Інтелектуальний роман Валерія Шевчука «Кросворд»: інтертекстуальні параметри - Мініч, Н. (Літературознавчі обрії. Праці молодих учених, 2010)
The article provides an intertextual analysis of an intellectual novel «Crossword» by one of the prominent Ukrainian writers Valeriy Shevchuk. The text of the novel is represented as the intertext of Ukrainian baroque and modern literature. The interpretation of the identified subtexts shows that the novel is not just an intriguing intellectual detective story, but a deep study of human nature and the phenomenon of love.